Doctrine that dances : bringing doctrinal preaching and teaching to life - Smith, Robert, 1949 May 26-; Massey, James Earl. (Nashville, Tenn. : B & H Academic, 2008)
Offering a lively look at a potentially arduous topic, Smith's intelligent, enthusiastic study on doctrinal preaching engages both the mind and heart. His illuminating insights on the impact biblical history, linguistics, moral conscience, and the transcendence of God have on doctrine will aid you in delivering messages that will point your listeners to a personal relationship with Christ. - Publisher.
Foreword / James Earl Massey -- Is there any word from the Lord? -- Toward a definition of doctrinal preaching -- A metaphorical rationale for doctrinal preaching -- Lord of the dance and the escort -- The preacher as an exegetical escort -- The preacher as a doxological dancer -- Maintaining doctrinal balance -- The jazz of doctrinal preaching -- Sermon 1 : "The other side of grace" Text: 2 Corinthians 12:1-10 -- Sermon 2 : "Living on the edge of whatever happens" Text: Philippians 1:1-2, 12-13, 19, 27.
Includes bibliographical references and indexes.
Keywords: Doctrinal preaching